Phytochemical Analysis and Antimicrobial Activities of Different Callus Extracts of Pelargonium Sidoides DC. Against Food Borne Pathogenic Bacteria - Mona M. Ibrahim, Salem Abd El Ghani, Sherein I. Abd El-Moez (Journal of Applied Pharmaceutical Science, 2018)
The objective of our study was to evaluate the secondary metabolites produced from callus culture of Pelargonium sidoides. This study was performed to, 1) evaluate the growth of Pelargonium sidoides DC. calli derived from different explants (leaf, root, and shoot tip), 2) to determine total phenolic, flavonoids and proanthocyanidin contents in aqueous methanol, water and aqueous acetone extracts of calli from different explants. Moreover, the antimicrobial activities of different extracts against food borne diseases caused by pathogenic bacteria were studied. The medium which contained 1.0 mg/l α-naphthalene acetic acid and 0.2 mg/l Kinetin was best to get friable calli with little brown deposits. The highest phenolic content was in calli from root extracted with aqueous acetone followed by calli from shoot tip extracted with the same solvent (12.34 and 4.78 mg/g DW) respectively. Also, the highest values of flavonoids content (20.82 mg/g DW) and Proanthocyandins (0.290 A550 nm/mg) were recorded with calli from root extracted with aqueous acetone. Antimicrobial effect of different calli extracts showed the maximum inhibition zone diameter (35 mm) was recorded with callus from shoot tip explants extracted with aqueous acetone against Clostridium perfringens ATCC.
Keywords: Pelargonium sidoides, Callus growth, Phytochemical analysis, Antimicrobial activities.